Can the completeness of radiological cancer staging reports be improved using proforma reporting? A prospective multicentre non-blinded interventional study across 21 centres in the UK. Issue 10 (2nd October 2018) - Patel, Anisha; Rockall, Andrea; Guthrie, Ashley; Gleeson, Fergus; Worthy, Sylvia; Grubnic, Sisa; Burling, David; Allen, Clare; Padhani, Anwar; Carey, Brendan; Cavanagh, Peter; Peake, Michael D; et al.
Abstract : Objectives: Following a diagnosis of cancer, the detailed assessment of prognostic stage by radiology is a crucial determinant of initial therapeutic strategy offered to patients. Pretherapeutic stage by imaging is known to be inconsistently documented. We tested whether the completeness of cancer staging radiology reports could be improved through a nationally introduced pilot of proforma-based reporting for a selection of six common cancers. Design: Prospective interventional study comparing the completeness of radiology cancer staging reports before and after the introduction of proforma reporting. Setting: Twenty-one UK National Health Service hospitals. Participants: 1283 cancer staging radiology reports were submitted. Main outcome measures: Radiology staging reports across the six cancers types were evaluated before and after the implementation of proforma-based reporting. Report completeness was assessed using scoring forms listing the presence or absence of predetermined key staging data. Qualitative data regarding proforma implementation and usefulness were collected from questionnaires provided to radiologists and end-users. Results: Electronic proforma-based reporting was successfully implemented in 15 of the 21 centres during the evaluation period. A total of 787 preproforma and 496 postproforma staging reports were evaluated. In the preproforma group, only 48.7% (5586/11 470) of key staging items were present compared with 87.3% (6043/6920) in the postproforma group. Thus, the introduction of proforma reporting produced a 78% improvement in staging completeness . This increase was seen across all cancer types and centres. The majority of participants found proforma reporting improved cancer reporting quality for their clinical practice . Conclusion: The implementation of proforma reporting results in a significant improvement in the completeness of cancer staging reports. Proforma-based assessment of cancer stage enables objective comparisons of patient outcomes across centres. It should therefore become an auditable quality standard for cancer care.